2016
DOI: 10.2147/dddt.s98200
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness comparison of lamivudine plus adefovir combination treatment and nucleos(t)ide analog monotherapies in Chinese chronic hepatitis B patients

Abstract: Background/aimLamivudine (LAM) plus adefovir (ADV) combination therapy is clinically efficacious for treating chronic hepatitis B (CHB) patients in China, but no pharmacoeconomic evaluations of this strategy are available. The aim of this study was to examine the cost-effectiveness of LAM plus ADV combination treatment compared with five other nucleos(t)ide analog monotherapies (LAM, ADV, telbivudine [TBV], entecavir [ETV], and tenofovir [TDF]).MethodsTo simulate the lifetime (40-year time span) costs and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In our study, adefovir and entecavir had no significant effect on TB ( Table 2 ), presumably because they are mainly eliminated via the kidney ( 16 , 28 , 30 ). Even in patients with advanced severe hepatitis, their metabolic burden for elimination seemed to be not great.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In our study, adefovir and entecavir had no significant effect on TB ( Table 2 ), presumably because they are mainly eliminated via the kidney ( 16 , 28 , 30 ). Even in patients with advanced severe hepatitis, their metabolic burden for elimination seemed to be not great.…”
Section: Discussionmentioning
confidence: 47%
“…Even in patients with advanced severe hepatitis, their metabolic burden for elimination seemed to be not great. Because of the resistance of lamivudine-only therapy and the cost-effectiveness of antiviral agents, combination therapy using lamivudine and adefovir is often recommended ( 30 34 ). In the present study, patients subjected to adefovir therapy after lamivudine indeed exhibited higher TB than those with adefovir alone ( Table 2 ), supporting the identified lamivudine effect on hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a cost-effectiveness study in China showed that LAM monotherapy or in combination with ADV is not cost-effective due the high frequency of genetic resistance which leads to higher costs over the course of disease. Conversely, first-line treatment with ETV was found to be the most cost-effective therapy due to its higher efficacy and low risk of resistance [26]. In 2017, the reimbursement schemes in China were updated to include ETV and tenofovir in the national basic medical insurance reimbursement list, which may reduce the cost burden on patients and increase the utilization of these NAs as preferred first-line therapies [1].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding country perspective, nearly 20 different countries conducted these published HE models. China undertook the largest share (reported in 13 of the 65 studies [27,31,32,34,56,69,[71][72][73][74][75][76][77]), closely followed by the US (10/65 [46-48, 51, 52, 64, 70, 78-80]) and the UK (7/65 [33, 43-45, 49, 54, 81]).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%